PEMODELAN SENGKETA KLAIM ASURANSI DI INDONESIA: PENDEKATAN GAME THEORY - Florentinus Nugro Hardianto (Bina Ekonomi, 2017)
The process of insurance claims begins when the insurer submits a claim to the insurance company until the decision stage of the court. In practice, a number of insurance claim processes face problems causing disputes. Badan Mediasi dan Arbitrase Asuransi Indonesia (BMAI) reported that during the period 2006-2016 there have been 618 cases of insurance disputes. This study aims to create a model of insurance cheating behavior based on game theory approach. The result of backward induction analysis yields eight propositions which explain that the cheating of insurance claim can be done either by the dishonest policy holder or the dishonest claim clerk.Keywords: backward induction, game theory, insurance claim, insurance dispute, modelling